The Success of Freshwater Aquaculture Program: Nile Tilapia or “Nila” Culture In Indonesia - Gustiano, Rudhy; Arifin, Otong Z; Subagja, Jojo; Kurniawan, Kurniawan; Prihadi, Tri H; Saputra, Adang; Ath-Thar, M H F; Cahyanti, Wahyulia; Prakoso, Vitas A; Radona, Deni; Kusmini, Irin I; Kristanto, Anang H (Zuriat, 2023)
This paper discusses the current status of tilapia aquaculture production, historical development based on the production growth, technological advances in genetic improvement and culture system, trade and product development, strategies, and policies in maintaining and improving national production. All data and information used in this manuscript were collected from available publications relating to the past and present status of tilapia cultivation in the country. Nowadays, Indonesia is the second-largest tilapia producer in the world with the contribution of about 25.89% to tilapia global production. In Indonesia, tilapia is the largest production among other cultured species. The annual growth production of tilapia is inccread 11.61% from 2011 to 2018. West Java Provinceis the largest tilapia producer followed by West Sumatra, South Sumatra, and Central Java. In the last six years, most of tilapia production comes from pond culture followed by floating cages, net cages, paddy fields, and pen culture. The success of tilapia culture is much influenced by technological improve in grow-out and genetic improvement of the local varieties. A side of that, trading and global market oriented are also established with various acceptable products. Tilapia aquaculture in Indonesia shows the succsess story of freshwater aquaculture program from nothing before 1990 to be something at present time. To maintain and increase the future production of tilapia, it needs strategies and policies in production and trade. The tilapia program maybe used as a role model for another economic imprortant freshwater species in Indonesia.